Hermetic Bags for the Storage of Maize: Perspectives on Economics, Food Security and Greenhouse Gas Emissions in Different Sub-Saharan African Countries - Dijkink, Bert; Broeze, Jan; Vollebregt, Martijntje (Frontiers in Sustainable Food Systems, 2022)
During storage, cereals and legumes are vulnerable to insects, rodents, and fungi, which can cause loss of weight, damage or discoloration of products, and/or toxin formation . Hermetic bags can prevent excessive insect infestation, and toxin formation. This paper presents an analysis of the effects of hermetic bags for the storage of maize on food loss reduction by insects and on net greenhouse gas (GHG) emissions, based on practical data from field trials. Their economic feasibility, by optimising the total income in markets with different price seasonalities in different sub-Saharan African countries, is analysed. The data of five field trials were combined and put in classes of 50 days of increasing storage time to get a realistic loss of produce during storage using regular bags (with or without the use of pesticides) and hermetic bags. The maize for storage trials were used as is, bought locally or used direct from the field. Scenario studies with standard storage, standard storage combined with pesticides and hermetic bag storage show significant losses by insects after 100 storage days for standard and standard with pesticides storage, whereas with hermetic bags, product losses are kept to a minimum of 2%. The economic analysis shows less clear-cut outcomes: the interventions’ effectiveness depends largely on the rate of seasonal price fluctuation of the commodity. For farmers’ personal consumption, when the quality is less critical, the use of hermetic bags is only more economical compared with other methods of storage for produce kept over 100 days. Since the quality of maize is well-preserved by the hermetic bag, the return on the investment is shorter when the maize is sold at the market. However, for countries with a low seasonal price gap, the investment cannot be recouped. As the use of hermetic bags is a good intervention for preventing food loss, it is best promoted not only for providing direct profits to farmers but also for health benefits, as bag use implies a lower need for pesticides and a possible reduction in aflatoxin intake.